PEMETAAN RISIKO MULTIBENCANA ALAM PADA INFRASTRUKTUR JALAN - Jaya Iskandar; Roi Milyardi; Cindrawaty Lesmana (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Road infrastructure as a means of transportation has an important role in the economy of a region. The ability of road infrastructure to serve the community is not only needed under normal conditions but is also needed when a disaster occurs as part of disaster resilience. One of the approaches that can be used in assessing disaster preparedness is mapping disaster risk on the road sections under review. In this research, a case study of disaster risk mapping was carried out on the Pasauran-Sp. Labuan - Cibaliung and Citereup-Tanjung Lesung, Banten Province which is divided into 11 road sections. Disaster risk mapping on roads in Padegelang is very much needed with disaster-prone locations making it very prone to disasters, especially floods, tsunamis, earthquakes, and landslides. The aim of this study is to map disaster risk based on the value of the multi-disaster risk index (floods, tsunamis, earthquakes, and landslides) on the Pasauran-Sp. Labuan-Cibaliung and Citereup-Tanjung Lesung. Disaster risk mapping is carried out using the procedures of Director General of Highways Circular Letter no. 12/SE/Db/2014 concerning Guidelines for risk analysis of natural disasters affecting roads and bridges. With this disaster risk map, it is hoped that it will be useful for stakeholders to make decisions related to disaster mitigation on these roads. The results of the multi-disaster disaster risk index values obtained from this study in sections 9, 10 and 11 have a low risk level, in sections 1,3,5 and 6 have a medium risk level, and in sections 2,4,7 and 8 have a high level of risk